Man in Hawaiian shirt - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a close-up of a man wearing a Hawaiian shirt in a bar. He may be a bartender as he appears to be behind the bar with the bottles of alcohol behind him.